Impaired estimated glomerular filtration rate and associated factors among adult patients living with HIV at Asella Referral and Teaching Hospital, Ethiopia: A cross-sectional study - Tamiru Adugna Dadi; Teshome Tola Bedada; Abdurke Dido Akako; Legesse Tadesse Wodajo; Sebona Girma Moges; Wubshet Abraham Alemu (PLoS ONE, 2026)
Background Human Immunodeficiency Virus (HIV) remains a major global health challenge, particularly in sub-Saharan Africa. It is a multisystem disorder with significant renal involvement. In Ethiopia, limited data exist on the prevalence of impaired estimated glomerular filtration rate among patients with Human Immunodeficiency Virus. Identifying associated factors is critical for implementing targeted interventions to preserve renal function. Methods An institution-based cross-sectional study was conducted among 252 adult patients living with Human Immunodeficiency Virus from October 1 to December 30, 2024 at Asella Referral and Teaching Hospital. Data were collected via structured questionnaires and medical record reviews. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with impaired glomerular filtration rate (estimated glomerular filtration rate <60 mL/min/1.73m 2 ). Result The prevalence of impaired glomerular filtration rate was 18.7% (95% CI: 14.0–23.0). Factors significantly associated with impaired glomerular filtration rate included age > 40 years (AOR = 3.26; 95%CI: 1.17–9.12), history of smoking (AOR = 4.68; 95% CI: 1.87–11.70), opportunistic infections (AOR = 5.93; 95% CI: 2.23–15.74), diabetes mellitus (AOR = 3.86; 95% CI: 1.47–10.12) and hypertension (AOR = 2.71; CI: 1.07–6.82). Conclusion The study found that around 19% of the studied population had impaired glomerular filtration rate. Targeted screening for kidney disease should focus on individuals older than 40years, smokers and those with opportunistic infections, diabetes mellitus or hypertension.